The Structural Model of Positive Organizational Behavior and Job Satisfaction with the Mediating Role of Job Stressors - Tayebe Rahimi Pordanjani; Ali Mohamadzade Ebrahimi; Masome ESLAMI (Shahid Sadoughi University of Medical Sciences, 2019)
Introduction: Job satisfaction is considered as an important factor for increasing efficiency and individual satisfaction in the organization. The purpose of this study was to test the structural model of positive organizational behavior and job satisfaction with the mediating role of job stressors. Methods: Research design was correlation through structural equation modeling (SEM) and the sample consisted of 150employees that working in university of Bojnord, who were selected by stratified random sampling method. Participants in this study were measured using occupational stress, psychological capital, and job satisfaction questionnaires. Reliability and validity all of the questionnaires were accepted. Structural equation modeling (SEM) through Amos-23 and SPSS-23 software packages was used for data analysis. In addition, Preacher and Hayes' SPSS Macro program was used for testing mediation. Results: The results showed that the proposed model fits the data properly. Positive organizational behavior has a direct effect on job satisfaction and job stressors (p<0.0001). Also, the mediating effect of job stressors in the relationship between positive organizational behavior and job satisfaction was confirmed (p<0.0001). Conclusion: Therefore, organizations can increase their job satisfaction by reducing job stressors and training and reinforcing positive organizational behaviors of their employees.